The Concept of Ulul Albab Character-Based Education in the Department of Civil Engineering to Achieve Sustainable Infrastructure - Sedayu, A.; Setiono, A. R.; Yustisia, V. W.; Aini, K.; Yustisia, V. W.; Syihabuddin, T. (Proceedings of the International Conference on Green Technology, 2026)
Character education is a distinctive feature of higher education institutions, grounded in the vision and mission they strive to achieve. Character education embodies the development of reliable human resources in cognitive, psychomotor, and affective aspects by strengthening local wisdom. These reliable human resources are expected to support Indonesia's development, especially in sustainable infrastructure. The provision of infrastructure to achieve national welfare and prosperity requires individuals with knowledge, skills, and positive behavioural attitudes. In addition, spiritual and mental strength also contribute. This paper examines the concept of Ulul Albab character education in one engineering department included in the same scientific cluster, namely Civil Engineering. The method used is a contextual and conceptual study of character education at the UIN Maulana Malik Ibrahim Malang campus. Analysis by presenting theoretical studies and previous studies on character education compared to the concept of UIN Maulana Malik Ibrahim Malang. State Islamic University of Maulana Malik Ibrahim Malang, under the management of the Ministry of Religious Affairs, has the characteristic of Islamic boarding school-based education. This campus strives to implement the Ulul Albab character, consisting of dhikr (dzikir), thought (fikr), and action (amal), in all academic and non-academic curricula. State Islamic University of Maulana Malik Ibrahim Malang, one of the Islamic religious universities, is supported by four pillars in realising the Ulul Albab character. The four pillars include spiritual depth, moral nobility, breadth of knowledge, and professional maturity. This is implemented across all levels, including faculties and departments. The of Department Civil Engineering, a field of engineering and applied science, requires support for implementing the four pillars that integrate religious values with civil engineering.